1975
DOI: 10.1139/o75-047
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Folic Acid Compounds in Nature. IV. Folic Acid Compounds in Soybeans and Cow Milk

Abstract: Folate compounds in soybean and cow's mild were identified by Sephadex chromatography and differential microbiological assaymsoybean contained mainly monoglutamates (ca. 52%), some diglutamates (ca. 16%), and polyglutamates (pentaglutamates representing the major portion). 5-CHO-H4PteGlun(1-6) constituted 65-70% of total folate activity; Cow's milk contained monoglutamates (60%) and polyglutamates (ranging from di- to hepta-conjugates). In contrast to soybean, 90-95% of milk folate was in the 5-CH3h4pteGlun(1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 2 publications
1
15
0
Order By: Relevance
“…The sustained expression of GCPII in the jejunal mucosa along with the decline in ileal mucosa during postnatal development is similar to that of other brush border membrane hydrolases, such as amino-oligopeptidase, which increases in jejunal mucosa and decreases in ileal mucosa at weaning in rats (24). Since milk folates are primarily found as 5-methyl-tetrahydrofolates in the polyglutamyl form (19,27), newborn pig intestine may express GCPII along the entire small intestine to maximize mucosal hydrolysis of the large influx of polyglutamyl folates from milk. At weaning (3 wk), piglets transition from milk polyglutamyl folates to monoglutamyl folic acid, which is found in pig chow.…”
Section: Discussionmentioning
confidence: 56%
“…The sustained expression of GCPII in the jejunal mucosa along with the decline in ileal mucosa during postnatal development is similar to that of other brush border membrane hydrolases, such as amino-oligopeptidase, which increases in jejunal mucosa and decreases in ileal mucosa at weaning in rats (24). Since milk folates are primarily found as 5-methyl-tetrahydrofolates in the polyglutamyl form (19,27), newborn pig intestine may express GCPII along the entire small intestine to maximize mucosal hydrolysis of the large influx of polyglutamyl folates from milk. At weaning (3 wk), piglets transition from milk polyglutamyl folates to monoglutamyl folic acid, which is found in pig chow.…”
Section: Discussionmentioning
confidence: 56%
“…The polyglutamyl chain in soybean contains about 50% monoglutamate and the rest is formed by di‐ to heptaglutamate, mainly in the form of 5‐formyltetrahydrofolate (85%) and 5‐methyltetrahydrofolate (15%) 20. The thermal stability of 5‐formyltetrahydrofolate was found to be much higher than that of 5‐methyltetrahydrofolate 21.…”
Section: Resultsmentioning
confidence: 99%
“…5-formyl THF together with 5-MTHF, 10-formyl folic acid and folic acid were identified in cereals (Pfeiffer et al 1997) whereas our study found only 5-MTHF in most of the cereal preparations (cooked parboiled rice, chapatti, poori, uppuma, noodles, bhelpuri, vegetable biriyani) with exceptions being homemade dosa and idli showing 5-formyl THF to be the predominant form, probably contributed by the black gram (Vigna mungo) dhal added to the preparation. Earlier studies on legumes have shown that 5-MTHF was the predominant form in soyabeans (Shin et al 1975) and lima beans (Seyoum and Selhub 1993). Differences in the methodology for analyzing the native folates, detection and quantitation limits can contribute to differences in the folate forms identified in the same samples.…”
Section: Analysed Folate Forms In Foods Using Lc-ms/msmentioning
confidence: 99%